Chinese Educational Policy Research: The Arduous Formation of a Research Paradigm. (December 2019) - Lin, Xiaoying
Purpose: Through combing the 40 years' history of the development of Chinese educational policy research, this article attempts to sort out the efforts and lessons learned by researchers in the field of education policy in China. Design/Approach/Methods: As one of the earliest scholars engaged in the study of Chinese education policy, based on the academic publications, symposia, and thematic research, the author has found efforts in four directions in the field: proposals for policy-oriented research and research-oriented policy, disciplinization-based endeavors, empirical research on theory-guided educational policy, and guidance on major educational policy research topics and a think tank for educational policy decisions. Findings: This article argues that there is now a correspondence among the ideas, themes, forms, and frameworks of the educational reform promulgated by the government in recent years that have appeared in educational policy research, but there is no clear demarcation of what makes an educational policy researcher; no stable academic community has been formed that might strive together toward the foundation of a disciplinary paradigm, the rational organization of academic ideas, and the establishment and handing over of a theoretical framework to a succeeding generation. Originality/Value: This article takes a step back to claim that a paradigm for Chinese educational policy research is still nascent in the arduous process of formulation.